(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the evidence found in the national and international scientific literature, regarding the process of death and dying in pediatrics in terms of academic training and practical experience of health professionals. This is an integrative review, supported by the PRISMA recommendation. The search was carried out from August to December 2020, through the databases: PubMed, LILACS, Scielo and CINAHL, applying the following filters: full articles published between 2010 and 2020, in English, Portuguese and Spanish and using the descriptors: “death/death”, health personnel/health personnel”, “child/child”, “patient care team/patient care team”. The final study sample consisted of 26 articles. In analyzing the publications, the articles were classified into three units of analysis, namely: the training process as a facilitator to deal with the process of death and dying, the experience of professionals in the face of family grief in pediatrics and terminality and palliative care in pediatrics. The study allowed us to state that the fact that death is still considered a taboo for society ends up perpetuating the lack of discussion and reflection on the process of death and dying in academia. Thus, health professionals do not feel effectively able to deal with the process of death and dying in pediatrics, mainly due to the lack of contact with this issue during undergraduate and even graduate studies and later, due to the lack of support in care institutions.